Effect of pinaverium bromide, trimebutine maleate and cisapride on interdigestive gallbladder volume and postprandial gallbladder emtying in normal subjects - Nadir YÖNETCİ and Serhat BOR and A. Ömer ÖZÜTEMİZ and Hakan YÜCEYAR and Galip ERSÖZ and Oktay TEKEŞİN and Tankut İLTER (Turkish Journal of Gastroenterology, 2020)
-